Importance of MRI in Showing the Early Period Erosive Alterations During Wrist Involvement in Rheumatoid Arthritis - Gökhan GÖKALP,; Zeynep YAZICI, (Archives of Rheumatology, 2011)
Objectives: In this study, we aimed to evaluate the efficacy of magnetic resonance imaging (MRI) in demonstrating erosive alterations during the early period of rheumatoid arthritis (RA). Patients and methods: Twenty-one wrists of 14 patients (11 females, 3 males; mean age 54 years; range 37 to 64 years) diagnosed with RA by clinical data and laboratory results were examined with MRI. The disease activity was determined by C-reactive protein and erythrocyte sedimentation rates. Wrist radiographies of all the patients were either normal or had suspicious signs. The presence of bone erosion was evaluated in 15 different regions (8 carpal bones, 5 metacarpal heads, 1 distal radius, and 1 distal ulna). Coronal and axial T1-weighted spin echo (SE) images with and without fat suppression, coronal T2-weighted turbo SE images with fat suppression, and coronal T1-weighted SE images with fat suppression following administration of intravenous gadopenteate dimeglumine were obtained. Results: In all cases, the wrist radiographs were either normal or exhibited suspicious findings. Bone erosion was found in 73 (81.1%) different sites in carpal bones, four different sites in distal radius (4.4%), four (4.4%) different sites in distal ulna, and nine (10%) different sites in proximal metacarpal heads. While capitatum (27.3%) and triquetrum (24.6%) were the most commonly affected sites, pisiforme (1.6) was found be the least affected site. Among the 21 wrist MRIs showing erosion, nine (42.8%) had synovitis, three (14.2%) had tenosynovitis, two (9.5%) had bursitis, and seven (33.3%) had bone marrow edema. Conclusion: Magnetic resonance imaging may be an effective diagnostic method for the determination of early period joint involvement in RA cases.